Effect of Basalt Size and Composition on Mechanical Properties of Wood Powder Polymer Biocomposite Material and Basalt as Reinforcement - Prabowo, Singgih; Astuti; Birawidha; Amin; Bahfie; Dwi Yanti; Savitri; Karo Karo; Irwanto (BRIN Publishing (Penerbit BRIN), 2024)
Utilization of waste for raw materials for new materials is very potential for research. Wood waste from door and window craftsmen is widely available as the property business develops. Wood waste mixed with polyester resin is modified by adding basalt to produce a biocomposite material with better mechanical properties. This research on the effect of adding the composition and size of basalt to the wood-polyester biocomposite material was studied to see changes in hardness values according to the ASTM E384 standard, compressive strength according to ASTM D695 standard, and its effect on density according to ASTM D1622 standard. The results showed that the higher the composition and the smaller the basalt hardness value, the compressive strength and density increased. The highest values of hardness, compressive strength and density were 36.6 HV0.5, 151.14 MPa, and 0.1420 kg/m3, an increase compared to that without the addition of basalt 26.7 HV0.5, 95.97 MPa, and 0.1288 kg/m3. Changes in the properties of hardness, compressive strength and density are taken into consideration in the formulation of using basalt to obtain new materials according to the desired specifications by utilizing wood waste.